Flagellin From Pseudomonas Aeruginosa Stimulates ATB0,+ Transporter for Arginine and Neutral Amino Acids in Human Airway Epithelial Cells - Barilli, Amelia; Visigalli, Rossana; Ferrari, Francesca; Borsani, Giuseppe; Dall'Asta, Valeria; Rotoli, Bianca Maria (Frontiers in Immunology, 2021)
The central role of arginine in the modulation of the inflammatory responses is, nowadays, well-recognized and many pro-inflammatory stimuli are known to modulate the expression and activity of its transmembrane transporters. In this regard, we here addressed the effects of bacterial flagellin from Pseudomonas Aeruginosa on the uptake of the amino acid in human epithelial respiratory cells. Among arginine transporters, only ATB0,+, y+L and y+ were actually operative in bronchial epithelial Calu-3 cells under control conditions; however, only the expression and activity of ATB0,+ were stimulated upon incubation with flagellin, while those of systems y+L and y+ did not. As expected, this induction lead, in turn, to an increase of the intracellular content of arginine without any change of its metabolic pathway. In addition the amount of other amino acids substrates of ATB0,+ was upregulated by flagellin, in particular all the essential amino acids, such as valine, isoleucine, and leucine along with the non-essential glutamine. At molecular level, these effects were directly referable to the stimulation of TLR5 signaling pathway and to the induction of NF-B transcription factor. An induction of ATB0,+ expression has been observed also in EpiAirway™, a model of primary human normal tracheal-bronchial epithelial cells that mimics in vitro the pseudostratified columnar epithelium of the airways. In this tissue, the incubation with flagellin associated with the up-regulation of mRNAs for the chemokine IL-8 and for the cytokines IL-6 and IL-1β; as for this latter, also a marked secretion in the extracellular medium was observed, due to the concomitant activation of caspase-1. Overall our findings indicate that, in human respiratory epithelium, flagellin promotes cellular responses that associate the increase of intracellular amino acids through ATB0,+ with the activation of inflammasome. Given the role of the transporter as a delivery system for bronchodilators in human airway epithelial cells, its induction under inflammatory conditions gains particular relevance in the field of respiratory pharmacology.